Factors associated with the efficacy of polyp detection during routine flexible sigmoidoscopy. Issue 2 (26th August 2017) - Maliampurakal, Akash J; McMillan, Donald C; Anderson, John H; Horgan, Paul G; Mansouri, David
Abstract : Objective: Flexible sigmoidoscopy reduces the incidence of colonic cancer through the detection and removal of premalignant adenomas. However, the efficacy of the procedure is variable. The aim of the present study was to examine factors associated with the efficacy of detecting polyps during flexible sigmoidoscopy. Design and patients: Retrospective observational cohort study of all individuals undergoing routine flexible sigmoidoscopy in NHS Greater Glasgow and Clyde from January 2013 to January 2016. Results: A total of 7713 patients were included. Median age was 52 years and 50% were male. Polyps were detected in 1172 (13%) patients. On multivariate analysis, increasing age (OR 1.020 (1.016–1.023) p<0.001), male sex (OR 1.23 (1.10–1.38) p<0.001) and the use of any bowel preparation (OR 3.55 (1.47–8.57) p<0.001) were associated with increasing numbers of polyps being detected. There was no significant difference in the number of polyps found in patients who had received an oral laxative preparation compared with an enema (OR 3.81 (1.57–9.22) vs 3.45 (1.43–8.34)), or in those who received sedation versus those who had not (OR 1.00 vs 1.04 (0.91–1.17) p=0.591). Furthermore, the highest number of polyps was found when the sigmoidoscope was inserted to the descending colon (OR 1.30 (1.04–1.63)). Conclusions: Increasing age, male sex and the utilisation of any bowel preparation were associated with an increased polyp detection rate. However, the use of sedation or oral laxative preparation appears to confer no additional benefit. In addition, the results indicate that insertion to the descending colon optimises the efficacy of flexible sigmoidoscopy polyp detection.